The reliability and minimal detectable change of various physical performance tests among youth basketball players - Krawczyk, Marcin; Siedlik, Daniel (Health Promotion & Physical Activity, 2022)
During a basketball game, the main motor activities performed by the players are running, jumping, sprinting and changing the direction of the run. These motor activities should constitute the main content of the battery of physical performance tests in basketball. Reliability and the minimal detectable change (MDC) in tests used in basketball are rarely reported in literature. The aim of the study was to fill this gap and an attempt to show the reliability and MDC of various tests among basketball players in the Cadet category. For this purpose, research was carried out in a group of 14 basketball players aged 15.3 years. Jumping tests, sprint test and a change of direction test were carried out. Based on the results of these tests, the index of reactive force, sprint momentum and the utilization index of the stretch-shortening cycle were calculated. The reliability and MDC of all tests, with the exception of the utilization rate of the stretch-shortening cycle, were at an acceptable level. In practical terms using of the procedure described in this study may provide valuable guidance in the analysis of changes in basketball players' physical performance.